RANCANGAN IMPLEMENTASI JARINGAN KOMPUTER BERBASIS ROUTER MIKROTIK STUDI KASUS PADA KAMPUS AMIK “BSI PONTIANAK” - Agung Sasongko (LPPM Universitas Bina Sarana Informatika, 2011)
Computers and networks are the outcome of the increasing needs of modern technology for computer users today. The increasing need for data transactions between computer users and practicality of data transfer to be one factor of the need for use computer network. Especially in an office that there are many employees who use computers as a tool of their work. In an Internet-connected offices are often faced problems with the speed of Internet access. Large bandwidth will always be perceived even less if bandwidth resources are not managed properly. Resource management is necessary especially for offices that have access points, to keep the Internet network connections remain comfortable it is necessary to design the network infrastructure and good management. Network management must be well planned on the office network infrastructure to optimize existing resources, including bandwidth management. with good bandwidth management, all units of computers connected to the office network to get internet access is equitable, so it is not the monopoly of the use of bandwidth for one user only, and jobs that require Internet connectivity to run better. Basically how much bandwidth that have if not properly managed then it will always be felt less. and the allocation of resources addressing the computer will be helpful for future maintenance and as a group within the office computer network.. Keyword: network, computer network, mikrotik, bandwidth management